Lemniscal and extralemniscal compartments in the VPM of the rat - Haidarliu, Sebastian; Yu, Chunxiu; Rubin, Naama; Ahissar, Ehud (Frontiers in Neuroanatomy, 2008)
The ventral posteromedial thalamic nucleus (VPM) of the rat contains at least two major vibrissa-representing compartments: the dorsomedial (VPMdm), which belongs to the lemniscal afferent pathway, and the ventrolateral (VPMvl), which belongs to the extralemniscal afferent pathway. Although input-output projections and functional characteristics that distinguish these two compartments were recently clarified, a comprehensive structural analysis of these compartments and the border between them was lacking. This paper addresses structural and functional relationships between the VPMdm and VPMvl. We found that the size of the VPM is almost constant across individual rats. Next, we computed a canonical map of the VPM in the oblique plane, where structural borders are best visualized. Using the canonical map, and sequential slices cut in oblique and coronal planes, we determined the border between the VPMdm and VPMvl in the standard coronal plane, and verified it with in-vivo extracellular recordings. The position of the border between these two vibrissal sub-nuclei changes along the rostrocaudal extent within the VPM due to the relative sizes of these sub-nuclei at any point. The border between the VPMdm and VPMvl, which was revealed by this technique, can now be included in atlases of the rat brain and should facilitate experimental correlation of tactile functions with thalamic regions.